2018
DOI: 10.1016/j.molcel.2018.09.031
|View full text |Cite
|
Sign up to set email alerts
|

MYC Protein Interactome Profiling Reveals Functionally Distinct Regions that Cooperate to Drive Tumorigenesis

Abstract: Highlights d Protein interaction screening identifies 336 MYC-interacting partner proteins d MB0 interacts with TFIIF to modulate transcription and accelerates tumor growth d MBII interacts with TRRAP-HAT complexes and is essential for tumor initiation d Co-expression of dysfunctional DMBII and DMB0 MYC proteins restores MYC activity

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
168
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 154 publications
(177 citation statements)
references
References 69 publications
8
168
0
1
Order By: Relevance
“…The mechanisms by which Yap/Taz and MYC coregulate transcription remain to be addressed: most noteworthy in this regard, these factors interact with an overlapping set of general coregulators (e.g., BRD4, p300, p400, RUVBL1, KMT2D, SAP18 or the SWI/ SNF complex). (39,40) As exemplified by BRD4, these coregulators may be involved in wider transcriptional programs than the transcription factors themselves, (41,42) but may nonetheless be particularly critical for transcription of genes activated by either Yap/Taz, (39) MYC, (43) or-even most likely-both together. (31) Although the involvement of MYC, WNT/βcatenin, and Yap/Taz in liver tumorigenesis was amply documented, (3,13,31,(44)(45)(46)(47)(48) their mutual interplay-if any-remained to be unraveled.…”
Section: Discussionmentioning
confidence: 99%
“…The mechanisms by which Yap/Taz and MYC coregulate transcription remain to be addressed: most noteworthy in this regard, these factors interact with an overlapping set of general coregulators (e.g., BRD4, p300, p400, RUVBL1, KMT2D, SAP18 or the SWI/ SNF complex). (39,40) As exemplified by BRD4, these coregulators may be involved in wider transcriptional programs than the transcription factors themselves, (41,42) but may nonetheless be particularly critical for transcription of genes activated by either Yap/Taz, (39) MYC, (43) or-even most likely-both together. (31) Although the involvement of MYC, WNT/βcatenin, and Yap/Taz in liver tumorigenesis was amply documented, (3,13,31,(44)(45)(46)(47)(48) their mutual interplay-if any-remained to be unraveled.…”
Section: Discussionmentioning
confidence: 99%
“…The upregulation of Myc could be present in various types of cancers, such as colon, breast, lung and gastric cancer [68]. To date, Myc and ANLN have been discovered to interact through experimental evidence, including affinity capture-MS [69], and proximity label-MS [70] and curated by the Biogrid [63].…”
Section: Other Binding Partnersmentioning
confidence: 99%
“…Among other actin-binding proteins present in the nucleus, FLi1 homolog, α-actinin 4, and filamin A are associated with SWI/SNF, estrogen receptor α, and BRCA 1, 2, respectively, and are involved in chromatin remodeling, transcription regulation, and DNA damage repair, respectively (Figure 4) [83]. ANLN is also known to bind transcription factors such as TAF10, Myc, and BRCA1, so ANLN is likely to be involved in chromatin organization, transcription, and DNA damage repair in the nucleus, respectively [70,92]. Recent reports found that the regulation of actin polymerization in the nucleus is required for transcription activation, cell cycle progression and DNA repair [106,107].…”
Section: Anln In Nucleusmentioning
confidence: 99%
“…All three MYC proteins have essentially the same overall domain structure, [74][75][76] consisting of…”
Section: Structurementioning
confidence: 99%